The Effects of Duration of Fermentation on Total Phenolic Content, Antioxidant Activity, and Isoflavones of The Germinated Jack Bean Tempeh (Canavalia ensiformis) - Tsalissavrina, Iva; Murdiati, Agnes; Raharjo, Sri; Lestari, Lily Arsanti (Universitas Gadjah Mada - Faculty of Pharmacy, 2023)
Tempeh is one of the food products from legumes often consumed by Indonesians as a side dish. Moreover, tempeh is a functional food that contains bioactive compounds, such as antioxidants and isoflavones. This study aims to determine the content of total phenolic compounds, flavonoids, antioxidant activity, and isoflavones content of germinated jack bean tempeh with a fermentation duration of 0-5 days. Isoflavones extract was obtained using the extraction method with 70 ethanol. The total content of phenolic compounds was measured using the method of Folin-Ciocalteau. Meanwhile, antioxidant activity was measured with DPPH, and isoflavones content was determined using high-performance liquid chromatography (HPLC). The total content of phenolic compounds (TPC), antioxidant activity, and isoflavones were analyzed using the ANOVA, and differences between treatments were compared to the Smallest Real Difference test with a significance level of 5. The total phenolic compound content and the highest antioxidant activity during the tempeh fermentation process were obtained on the fifth day of the fermentation period of 10.70±0.31 (mg GAE/g) for the total phenolic and 457.04±151.91() for IC50 values. The intergroup test results show significant differences. The highest isoflavones deposits for all isoflavones, such as daidzein, glycitein, genistein, and factor-2, were also obtained at day 5 of tempeh fermentation duration. This study has discovered significant differences between treatment groups. The isoflavones content is 4.63±1.74 µg/g of daidzein, 5.45±2.29 µg/g of glycitein, 0.92±0.33 µg/g of genistein, and 0.46±0.21µg/g of factor-2. This study has discovered that the germination and fermentation process of jack bean tempeh changes the content of total phenolic compounds and antioxidant activity as well as increases and influences the isoflavones profile. Copyright © 2023 by Indonesian Journal of Pharmacy (IJP).